Opportunities of additive technologies in the manufacture of high-tech products of mechanical engineering and biomedical engineering - S.V.; V.A. (Технічна інженерія, 2022)
Additive technologies are relatively new for the field of mechanical engineering, but they are extremely relevant and promising. Understanding the possibilities of such technologies and determining their place among established technologies is an important task today. The article analyzes the place of additive technologies, their capabilities in terms of shaping, creating extremely complex parts with a developed internal structure and surface structures. The possibilities provided by multi-material additive technologies are considered. The reasons for the paradoxical property of additive technologies to be invariant for the complexity of details are explained. The main opportunities and trends in the use of additive technologies in the design and manufacture of high-tech parts in mechanical engineering and biomedical engineering are analyzed.